Stable terahertz toroidal dipolar resonance in a planar metamaterial. Issue 6 (11th March 2015) - Ding, Chunfeng; Jiang, Linkun; Sun, Chongling; Wu, Liang; Xu, Degang; Zhang, Guizhong; Yao, Jianquan
<x xml:space="preserve">Abstract</x> In this paper, we proposed and fabricated a planar terahertz (THz) metamaterial that is composed of four asymmetric split‐ring resonators (ASRRs) coated with two polyimide layers. Simulation and experimental results show that a Fano‐shaped toroidal dipolar resonance at 0.42 THz is acquired from the metamaterial. Further analysis indicates that the toroidal dipolar resonance originates from the coupling of the four ASRRs, and the polyimide coating layers on both sides of the structure play key role in keeping the resonance frequency unchanged. From the designed metamaterials, a confined electromagnetic field inside the dielectric medium with a subwavelength‐scale toroidal geometry is observed, and a strong confined E‐field component at the toroidal dipole center with its orientation perpendicular to the H‐vortex plane can also be numerically acquired. This planar metamaterial would open up an avenue for potential applications in the terahertz regime.